2004
DOI: 10.1080/00039420410001667539
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of milk energy by suckling mink kits

Abstract: A total of 36 mink dams and their litters of 3, 6 or 9 kits were used for determination of milk intake of the suckling young by means of deuterium dilution technique, and chemical composition of milk and of kit bodies. Measurements were performed during lactation weeks 1-4, each week with 3 dams with each litter size. Milk intake was determined over a 48 h measurement period, and by the end of this milk samples were collected and 2 kits (litters of 6 and 9) or 1 kit per litter (litters of 3) were killed for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
2
8
1
1
Order By: Relevance
“…Another important condition to consider is whether milk composition was affected by dietary interventions. In the present study, dry matter and fat contents of milk increased during lactation, as previously found in mink (Olesen et al., 1992; Fink et al., 2001,2004; Tauson et al., 2004), cats (Dobenecker et al., 1998) and mice (Knight et al., 1986). However, the chemical composition of milk was not significantly affected by dietary treatment and milk yield, corresponding to results in foxes (Rusanen and Valtonen, 1991; Ahlstrøm, 1992), dogs (Scantlebury et al., 2000) and pigs (Auldist et al., 1998).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another important condition to consider is whether milk composition was affected by dietary interventions. In the present study, dry matter and fat contents of milk increased during lactation, as previously found in mink (Olesen et al., 1992; Fink et al., 2001,2004; Tauson et al., 2004), cats (Dobenecker et al., 1998) and mice (Knight et al., 1986). However, the chemical composition of milk was not significantly affected by dietary treatment and milk yield, corresponding to results in foxes (Rusanen and Valtonen, 1991; Ahlstrøm, 1992), dogs (Scantlebury et al., 2000) and pigs (Auldist et al., 1998).…”
Section: Discussionsupporting
confidence: 90%
“…The estimate of MEm by using milk intake per g body gain and recalculation to ME intake gave an estimate of 458 kJ/kg 0.75 , which is higher than our previous estimate of 356 kJ/kg 0.75 (Fink et al., 2001) and estimates for suckling kittens (356 kJ/kg 0.75 , Hendriks and Wamberg, 2000), and dog puppies (334 kJ/kg 0.75 , Mundt et al., 1981) but in good agreement with more recent results in mink (448 kJ/kg 0.75 , Tauson et al., 2004; and 456 kJ/kg 0.75 , own unpublished results). Utilisation of milk for body gain gave a k g value of 0.71 which is in close agreement with results in suckling pigs (Lawrence and Fowler, 1997), kittens (Hendriks and Wamberg, 2000) and mink (Tauson et al., 2004) in which k g ‐values of 0.65, 0.71 and 0.67, respectively, have been reported.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Fat in diets and faeces was determined by petroleum ether extraction after HC1 hydrolysis, and gross energy (GE) by use of an adiabatic bomb calorimeter. In milk samples, fat was analysed by a method slightly modified from Baverstock et al (1976) as described by Tauson et al (2004), and GE was calculated by use of the data for milk composition and the energy factors (in kJ/g): protein (23.9), fat (39.8) and carbohydrates (17.6). In all samples, contents of carbohydrates (CHO) were calculated by difference (CHO = DM -ash -CP -fat).…”
Section: Analytical Procedures Feed Excreta and Milkmentioning
confidence: 99%
“…Olesen et al. (1992) and Tauson et al. (2004) found no change in the protein content, whereas Fink et al.…”
Section: Introductionmentioning
confidence: 94%